Impact of minimalism on consumers’ low-carbon innovation behavior: Interactive role of quantitative behavior - Jian Gao; Liyu Tang; Yang Lyu (Chinese Journal of Population, Resources and Environment, 2023)
Minimalism has become a new consumer trend that can guide low-carbon innovation behaviors. This study uses two experiments and one survey to explore the mechanisms underlying the relationships among minimalism, quantitative behavior, and low-carbon innovation behavior. The results show that (1) minimalism can positively influence consumers’ low-carbon innovation behavior; (2) the interactive effect of minimalist and quantitative behavior on low-carbon innovation behavior is significant; and (3) meaning in life can play a significant mediating role in the relationship between minimalism and low-carbon innovation behavior. Finally, corresponding strategies for theory and management practices are proposed.